Hepatitis B, hepatitis C and HIV in Irish Prisoners: prevalence and risk - BARRY, JOSEPH; ALLWRIGHT, SHANE PATRICIA ANN (The Stationery Office, 1999)
A cross sectional survey of hepatitis B, hepatitis C and HIV prevalence in the Irish prisoner population was undertaken. The study was carried out in nine prisons, five of which had been classified as high risk and four as medium risk for infection. All the high risk prisons were in Dublin while the medium risk prisons were outside Dublin. Overall there was excellent cooperation with the survey; the response rate was 88%. A total of 1,205 prisoners took part in the survey, which consisted of completing a four page questionnaire and collecting a sample of oral fluid for testing for antibodies to hepatitis B, hepatitis C and HIV. The fieldwork for the study was carried out between September and November 1998.
PUBLISHED
Keywords: Public Health; HIV